1996
DOI: 10.1080/0013191960480301
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Child Psychology to Religious Curricula: the cautionary tale of Goldman and Piaget

Abstract: The curriculum in British schools began to show the influence of child psychology in the 1960s and this influence was exemplified in Ronald Goldman's attempt to apply Piagetian psychology to religious education. Goldman's work attempted to transfer Piagetian theory to the interpretation of texts, an attempt to which Piagetian theory is particularly ill-suited. Nevertheless, it would be a mistake to underrate the contribution which child psychology might be expected to make to religious curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…We believe this is timely since research into pedagogic issues in teaching religious education in English primary schools is an underdeveloped area. As Kay (1996) argued, there have been few challenges to research in religious education premised on constructivism and Watson (1993) has suggested a more optimistic approach might be entertained, whilst Cooling (1996) reflected an awareness of a research that engages with processes as well as learning outcomes. Hay, Nye and Murphy (1996) suggested the importance of identifying signals of transcendence in children's speech.…”
Section: Introductionmentioning
confidence: 97%
“…We believe this is timely since research into pedagogic issues in teaching religious education in English primary schools is an underdeveloped area. As Kay (1996) argued, there have been few challenges to research in religious education premised on constructivism and Watson (1993) has suggested a more optimistic approach might be entertained, whilst Cooling (1996) reflected an awareness of a research that engages with processes as well as learning outcomes. Hay, Nye and Murphy (1996) suggested the importance of identifying signals of transcendence in children's speech.…”
Section: Introductionmentioning
confidence: 97%